Analisis Penggunaan Metode User-Centered Design dalam Peningkatan Akseptabilitas SIMPELMAS - Muhammad Imam Ghozali; Alif Catur Murti; Syafiul Muzid (STMIK Budi Darma, 2023)
In the digital era and the development of information technology, websites have become a crucial platform in the higher education environment. The website provides various information, services and interactions between educational institutions and students, lecturers and staff. In this context, the use of UI/UX analysis on websites is becoming increasingly important to provide optimal user experience. The User-Centered Design (UCD) method is an effective approach in analyzing UI/UX on websites. UCD puts users at the center of attention throughout the design process, from understanding requirements to evaluation. By collecting data about users, creating personas, identifying user needs, and involving users in prototype development and testing, UCD helps gain a deep understanding of users and their needs. The results of this research can provide valuable insights for developers, designers, and educational institutions in improving user experience and website effectiveness. The importance of developing a responsive and user-friendly design to meet user needs and provide an optimal experience in using the website